(untitled) (International Journal of Studies in Nursing, 2024)
The aim of this study was to explore and define the spiritual needs of older residents in long-term care facilities (LTCFs) using the Walker and Avant (2019) approach. In this regard, the keywords “spiritual needs”, “old adults” and “long-term care facilities” were searched through PubMed, EBSCOhost, and Google Scholar electronic databases between the years 2000 and 2023 along with hand searching of reference lists extracted from more than 135 articles. Finally, 11 articles that had inclusion criteria were examined based on the eight stages mentioned in Walker and Avant’s concept analysis approach. Through the systematic application of Walker and Avant’s eight stages concept analysis approach, this paper provides a nuanced understanding of the spiritual needs of elderly residents in long-term care facilities. The results are serves as a valuable tool for guiding caregivers, healthcare professionals, and policymakers in developing strategies that cater to the spiritual well-being of this demographic, ultimately fostering a more holistic and compassionate caregiving environment.